2010
DOI: 10.1111/j.1750-3841.2010.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changes in Sugar Exudate Created by Biological Damage to Tomato Plants on the Persistence of Escherichia coli O157:H7

Abstract: The survival of enteric pathogens on vegetable leaves improves due to presence of phytopathogens. Phytopathogen damage alters the microenvironment on the leaf surface. The objective of this study was to identify differences in sugar concentrations in tomato leaves damaged by biotropic plant pathogens and determine if these differences affect Escherichia coli O157:H7 survival. E. coli O157:H7 survived better on tomato plants damaged by Xanthomonas campestris than on healthy plants (P = 0.012). The most common s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…In fact, supermarket surveys established that human pathogens are significantly more likely to be found in produce affected by bacterial soft rot than in lesions caused by mechanical damage or fungal pathogens (9). Follow-up laboratory studies supported conclusions of supermarket surveys and demonstrated that within soft rots, S. enterica and E. coli reach cell numbers that are 10 to 1,000 times higher than those in intact plants (7,(10)(11)(12)(13). The effects of phytobacteria on human pathogens occupying the same niche are significant not only in the magnitude of their growth increase but also in the breadth of physiological adaptation to the cohabitation.…”
supporting
confidence: 49%
See 3 more Smart Citations
“…In fact, supermarket surveys established that human pathogens are significantly more likely to be found in produce affected by bacterial soft rot than in lesions caused by mechanical damage or fungal pathogens (9). Follow-up laboratory studies supported conclusions of supermarket surveys and demonstrated that within soft rots, S. enterica and E. coli reach cell numbers that are 10 to 1,000 times higher than those in intact plants (7,(10)(11)(12)(13). The effects of phytobacteria on human pathogens occupying the same niche are significant not only in the magnitude of their growth increase but also in the breadth of physiological adaptation to the cohabitation.…”
supporting
confidence: 49%
“…Salmonella appears to be able to repurpose the strategies it uses to obtain nutrients in the intestine in order to gain 1,2-propanediol and ethanolamine from soft rots (12). Nevertheless, mechanisms by which these enteric pathogens take advantage of the presence of phytopathogens only now are beginning to be understood (7,12,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrigation water is considered a potentially important introduction route, and several studies have shown its potential for the transmission of enteric pathogens to lettuce plants. However, most of these studies were conducted either under laboratory or controlled conditions in growth chambers (Brandl and Mandrell, 2002;Solomon et al, 2003;Aruscavage et al, 2008;Aruscavage et al, 2010;Brandl and Amundson, 2008;Zhang et al, 2009;Erickson et al, 2010a) or field experiments (Barker-Reid et al, 2009;Erickson et al, 2010b;Harapas et al, 2010;Wood et al, 2010;Fonseca et al, 2011). Few studies have compared both types of experimental setups.…”
mentioning
confidence: 99%